Running shoes-possible correlations of biomechanical and material tests - Eckelt, M.; Mally, F. (Proceedings, 2020)
Today`s development of running shoes is often supported by the assessment of biomechanical tests (BIOs) as well as material tests (MATs). In order to possibly reduce the number of relevant tests, the aim of this study was to find out whether there are correlations between the selected BIO and MATs. Therefore, four different running shoes were tested. For the BIO, the ground reaction force and tibial acceleration of 19 experienced runners were measured. The evaluated parameters were first peak, time to first peak, impulse during the first 75 ms of stance, maximum vertical ground reaction force, loading rate, mean peak acceleration and median power frequency. The MATs included compression tests and an impact test with and without insoles at the forefoot as well as the heel area. The results show that carrying out MATs (especially impact tests) without insoles give the most insight into the parameters analysed with the BIO.